Pengaruh Kematangan Iman Terhadap Kesediaan Menghidupi Panggilan Dengan Nilai Materialistik Sebagai Moderator - Dorkas, Mopheta Audiola; Yuliawati, Livia (Psychopreneur Journal, 2020)
Living calling in career means a condition in which a person is able to live up to what has become his vocation so that they're able to live a career or work done more positively. In some phenomena that occur among priests, the willingness to living a calling is still largely influenced by external factors that make it difficult for them to living a calling. The hypothesis of this study is that faith maturity influences living calling with materialistic value as a moderator. The research method uses a quantitative survey approach with quantitative correlational research techniques between three variables. The research subjects were 47 priests and vicar in one church synod in Bali and obtained by total population study technique. Data analysis using the linear regression analysis correlation test and correlation test. The conclusion of this study is that there is a positive influence of faith maturity on living calling but materialistic value cannot be a moderator